Stress Testing Household Debt in Korea - Karasulu, Meral (IMF Working Papers; Working Paper, 2008)
Korean household debt has reached 148 percent of disposable income, high by emerging market standards. Most of this debt remains at variable rates, shifting the interest rate risk from better diversified financial institutions to households and increasing their sensitivity to macroeconomic shocks. This paper examines the sources of, and risks from, household debt by employing stress tests on household level panel data. Results suggest that a 100-300 bps increase in interest rates could increase distressed household debt household debt by 8 1\2 ?17 percentage points (ppt). A drop in real estate prices by 10?30 percent could add another 4 ppt to distressed debt. Ongoing transition to amortizing mortgages in 2008?09 presents additional challenges as interest payments on debt are likely to increase further.